Rancang Bangun Game Simulasi Pemrograman Berbasis Obyek (PBO) Sebagai Media Pembelajaran Mahasiswa Teknik Informatika Universitas Muhammadiyah Sidoarjo - Cindy Taurusta; Yulian Findawati (Institut Seni Indonesia Yogyakarta, 2018)
Technological progress is increasing rapidly along with the increasing need for graduates of Informatics Engineering in Higher Education. Many companies and businesses today require graduates who can compete in terms of programming. And the most dominant programming that must be mastered by the graduates of Informatics Engineering is Object-Based Programming (PBO) or commonly known as Java Programming. Where this programming is programming that can generate various applications, both applications in Personal Computer (PC) and in mobile. However, based on analysis conducted by the researcher when teaching object-based programming program (PBO) in Informatics Engineering Faculty of Engineering Muhammadiyah University of Sidoarjo, found the result that there are still many students who still difficulty studying this course, if only taught through theory without any direct practice. So that students interested in studying this subject further and learning not only through theory, a fun learning will researchers do by making the Design of Object-Based Programming Simulation Game (PBO) As Media Student Learning Informatics University of Muhammadiyah Sidoarjo. This game will contain several learning levels packed with animation. Where players are students not only get learning about what components are required in programming Java, but also steps - steps programming Java easily presented with an interesting animation. Not only the curiosity and excitement in playing but understanding and making the program easier. The purpose of making this learning simulation game in order to help Student of Informatics Engineering Muhammadiyah University of Sidoarjo in understanding, likes, and able to make object-based program or Java so as to improve the quality and competitiveness of Informatics Engineering Student University of Muhammadiyah Sidoarjo in the world of work. And in the future, researchers will conduct a survey to prove the effects and results obtained after learning through simulation games. Keywords: Simulation Game, Animation, IT Student, Object-Based Programming, Java